Peter L. Berger and the sociology of religion: 50 years after the Sacred canopy - Hjelm, Titus (Bloomsbury Publishing PLC, 2018)
Intro -- Title Page -- Copyright Page -- Contents -- List of Contributors -- Preface and Acknowledgements -- Chapter 1: Introduction: Peter L. Berger and the Sociology of Religion -- Sociology of religion and sociology of knowledge -- Elements of a sociological theory of religion -- Secularization and desecularization -- Engaging Berger -- Chapter 2: Vulnerability and Plausibility Structures: Peter L. Berger, Arnold Gehlen and Philosophical Anthropology -- Gehlen and Berger on institutions -- The ambiguities of Berger's notion of 'facticity' -- Vulnerability and fragility -- Conclusion: On changing one's mind -- Chapter 3: From Canopies to Conversations: The Continuing Significance of 'Plausibility Structures -- The power of conversation -- Religion beyond consciousness -- Chapter 4: The Sacred Canopy as a Global Construction Project: Incorporating both Emotional and Cognitive Resources -- The Sacred Canopy's intellectual context -- Innate sociality -- Religious pluralism versus monopolies -- Global universalism versus multiple particularisms -- Conclusion -- Chapter 5: The Sacred Canopy as a Classic: Why Berger's Conceptual Apparatus Remains Foundational 50 Years Later -- Part 1 of The Sacred Canopy: The systematic elements -- A lesson from Durkheim scholarship: Ideas are contagious -- A wide range of applications: Notes from a young Bergerian -- Conclusion: A legacy half-achieved -- Chapter 6: Sacred Canopies and Invisible Religions: The Dialectical Construction of Religion in Berger and Luckmann -- Religion and Berger's biography -- The Social Construction of Reality and religion -- Luckmann's Invisible Religion -- From The Sacred Canopy to The Many Altars of Modernity -- The dialectics of Berger and Luckmann -- Conclusion -- Chapter 7: Secularization: From Sacred Canopies to Golf Umbrellas -- Secularization in The Sacred Canopy